Faktor-Faktor Yang Berpengaruh Terhadap Kecenderungan Kecurangan Akuntansi Pada BUMN di Kota Ambon - Dwi Kriswantini; Elna Marsye Pattinaja; Hempry Putuhena (Postgraduate, University of Mataram, 2023)
The purpose of this study was to analyze the factors of internal control effectiveness, appropriateness of compensation, observance of accounting rules, information asymmetry and management morality that influence the tendency of accounting fraud. The research data is primary data collected by directly distributing questionnaires to BUMN in Ambon City. The samples in this study were employees or employees in the accounting, finance and treasurer departments. The results of empirical testing using multiple regression analysis show that the effectiveness of internal controls, appropriateness of compensation, observance of accounting rules, management morality have no influence on the tendency of accounting fraud. Meanwhile, information asymmetry has a positive influence on the tendency of accounting fraud. The conclusions that can be obtained are 1) This study proves that there is an influence between information asymmetry on the tendency of accounting fraud, these results are consistent with previous research. In addition, this research is also in line with previous research which states that the suitability of compensation has no effect on the tendency of accounting fraud. 2) However, this study found things that contradict the hypotheses and theories and results of previous studies, that the effectiveness of internal controls, observance of accounting rules and management morality are not able to reduce the tendency of accounting fraud. This is due to a lack of awareness of the importance of internal control and accounting rules within the company